Endovascular Treatment of Wide-Neck Middle Cerebral Artery Aneurysms with Stents: A Review of 16 Cases - Yang, P.; Liu, J.; Huang, Q.; Zhao, W.; Hong, B.; Xu, Y.; Zhao, R. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: MCA aneurysms are common and often pose technical challenges to interventionalists. Intracranial stents are widely used in treating wide-neck aneurysms in other locations. To evaluate the feasibility, effectiveness, and safety of stent placement in MCA aneurysms, we performed this retrospective study. MATERIALS AND METHODS: Between October 2003 and May 2009, 16 patients with 16 wide-neck MCA aneurysms were treated with stents at our institution. We retrospectively collected and analyzed the data for these patients, including demographics, morphologic features of the aneurysms, treatment results, and follow-up. RESULTS: Seventeen stents, including 12 Neuroform, 4 LEO, and 1 Enterprise, were successfully deployed in this series. Of the 13 aneurysms treated with stent-assisted embolization, complete occlusion was achieved in 9 aneurysms; residual neck remained in 1, and residual aneurysm was present in 3. Contrast stasis in the aneurysm sac was observed in the other 3 aneurysms treated with stent alone. Procedure-related complication occurred in 1 patient, leading to no permanent effect. The mRS score at discharge was 0–2 in 14 patients and 3–6 in 2. The angiographic follow-up results of 9 patients (mean, 5.6 months) showed that all aneurysms remained stable or improved; there was no in-stent stenosis, recurrence, or retreatment. The clinical follow-up (mean, 20.1 months) demonstrated no neurologic deterioration or rebleeding. CONCLUSIONS: Our preliminary experience demonstrates that stent placement for the treatment of selected wide-neck MCA aneurysms is feasible. However, its safety and efficacy should be further evaluated by larger case series and more adequate follow-up. BifurbifurcationDSAdigital subtraction angiographyEPEnterpriseFUfollow-upHH ScaleHunt and Hess ScaleLleftL in “Size” columnlargemmonthMCAmiddle cerebral arteryMRAMR angiographymRSmodified Rankin ScaleNAnot applicableNFNeuroformRrightSsmallTtiny